EVALUATION OF INTERNAL AND EXTERNAL FACTORS AFFECTING THE DEVELOPMENT OF SEMI-INTENSIVE BEEF CATTLE FARMER GROUPS INTEGRATED WITH OIL PALM PLANTATIONS IN CENTRAL BANGKA REGENCY - Mohammad Hasan Bisri; Novie Andri Setianto; Muhammad Bata; Yusmi Nur Wakhidati; Efka Aris Rimbawanto (Jurnal Ternak, 2026)
This study aimed to evaluate the internal and external factors influencing the development of these integrated enterprises in Central Bangka Regency. The research was conducted on 21 cattle groups using a survey approach, field observations, structured interviews, and an assessment of internal and external factors. Data were analysed using the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. The results showed a total IFE score of 2.801, indicating a relatively strong internal position, with primary strengths being member motivation, land carrying capacity, and the utilization of oil palm by-products as feed. The total EFE score of 2.680 suggests a supportive external environment. Key opportunities include local government policy support, the role of extension agents, and market demand for beef, while primary threats involve rising prices of commercial feed and veterinary medicines, competition from beef supplied by other regions, and instability in local beef supply. Enterprise development should focus on strengthening capital, feed technology, institutional frameworks, and marketing systems.